Anaesthetic challenges in perioperative management of thoracic paraganglioma in an 8-year-old child. Issue 8 (5th August 2021) - maurya, Ram Gopal; Gautam, Shefali; Singh, Gyan Prakash; srinivas, Chaitra
Abstract : Pheochromocytomas (PCC) are catecholamine-secreting tumours that arise from chromaffin cells of the sympathoadrenal system. These rare catecholamine-secreting tumours arising from adrenal glands are termed as PCC and those from extra-adrenal sites are termed paraganglioma (PGL). Thoracic PGL is very rarely found. we report the anaesthetic challenges and management of an 8-year-old child with functional thoracic PGL and its successful outcome.